Economics of Mushroom (Agaricus bisporus) Production in a Selected Upazila of Bangladesh (The Agriculturists, 2012)
A study was conducted during 2011 to estimate profit, benefit cost ratio (BCR) and household income of mushroom production and also to explore the problems of producing mushroom and its marketing channels in Bangladesh. Thirty samples were randomly selected and information on mushroom production was collected using comprehensive questionnaire from Savar Upazila in Dhaka district. Mushroom was found to be a profitable agricultural enterprise (22,888 taka per farm). The benefit cost ratio (BCR) was 1.55. The average family household income was about Tk. 43,731. Usually, three intermediaries (mushroom office, wholesalers and retailers) are involved in the marketing channels of mushroom. The marketing margin of mushroom for farm-gate to wholesalers and wholesalers to retailers were taka 50 and 70 per kg, respectively. It was revealed that rich and middle income group people were the main mushroom customers. Even though mushroom is a profitable enterprise, the producers faced numerous problems regarding mushroom production and marketing. DOI: http://dx.doi.org/10.3329/agric.v10i2.13144 The Agriculturists 2012; 10(2) 77-89